Non-invasive Foetal ECG – a Comparable Alternative to the Doppler CTG? - Reinhard, J.; Louwen, F. (Geburtshilfe und Frauenheilkunde, 2012)
This review discusses the alternative of using the non-invasive foetal ECG compared with the conventionally used Doppler CTG. Non-invasive abdominal electrocardiograms (ECG) have been approved for clinical routine since 2008; subsequently they were also approved for antepartum and subpartum procedures. The first study results have been published. Non-invasive foetal ECG is especially indicated during early pregnancy, while the Doppler CTG is recommended for the vernix period. Beyond the vernix period no difference has been recorded in the success rate of either approach. The foetal ECG signal quality is independent of the BMI, whereas the success rate of the Doppler CTG is diminished with an increased BMI. During the first stage of labour, non-invasive foetal ECG demonstrates better signal quality; however during the second stage of labour no difference has been identified between the methods.
Keywords: obstetrics; fetal ECG; Doppler CTG